The role of ethical school leadership in developing and promoting trust and accountability: a case study of two secondary schools in Johannesburg - Cindi, Fortunate (My University, 2021)
This qualitative and interpretivist study sought to investigate the role of ethical school leadership in developing and promoting a work culture built on trust and accountability. Given the voluminous studies that have been carried out by different authors on the philosophy of ethical leadership, literature reviewed for the purpose of this study revealed that there is still insufficient research on how this phenomenon highly influences ‘trust’ nd ‘accountability’. Consequently, this study acted as a point of departure from the present research on ethical leadership which focuses more on its potential impact in curbing corruption, rather than its extensive role in promoting trust and accountability. This study is based on research that was conducted in two secondary schools found within the Johannesburg Central District in Soweto, Gauteng Province-thus contributing to the existing body of knowledge in terms of ‘context’. Two school principals, four heads of department and eight Post Level 1 teachers were purposefully and conveniently identified to participate in the study. An amalgamation of the concepts of ethical leadership, trust and accountability formed the framework as deemed a useful lens to interrogate the generated data. Data generated through triangulation of semi-structured interviews, documents review and observations was thereafter presented, analysed and discussed. The findings indicated that participants possessed an adequate understanding of ethics-which helped them to conceptualise the phenomenon of ethical leadership. However, there was a prevalent culture of mistrust and lack of accountability in the researched schools. The issues that led to mistrust and lack of accountability were multifarious and ranged from ineffective communication, exclusion, bias, or favouritism (i.e., evident through nepotism), lack of ethical leadership traits that build the foundation of trust to exploitation by school principals and futile accountability measures that implicitly encouraged unethical behaviour. Ethics education for pre-service and in-service educators, team building and dismantling of principal power in recruitment processes was therefore recommended
A research report submitted in partial fulfilment of the academic requirements for the degree of Master of Education (by Course Work and Research Report) to the Faculty of Humanities, Wits School of Education, 2021